Powdery composite positive electrode active material, lithium ion battery positive plate containing powdery composite positive electrode active material and lithium ion battery
Through the powder atomic layer deposition process, a uniform and controllable LiF cladding layer is formed on the high-nickel ternary material, which solves the problem of electrolyte erosion and cladding layer control difficulty, and improves the cycle life and performance of lithium-ion batteries.
Patent Information
- Application Number
- CN202411928433.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing high-nickel ternary material lithium-ion battery positive electrode material is easily eroded by electrolyte at high voltage, resulting in a decrease in energy density and cycle life. It is difficult to control the uniformity and thickness of the LiF coating layer, which affects battery performance.
The high nickel ternary material with a uniform thickness and controllable LiF coating layer was synthesized at lower temperatures using powder atomic layer deposition (PALD) process to ensure that the thickness of the lithium fluoride coating is in the range of 1 nm to 1000 nm.
It improves the interface stability of the positive electrode material of lithium-ion battery, inhibits the growth of SEI film, extends the cycle life of the battery, and optimizes the performance and safety of the battery.
Smart Images

Figure CN119742339A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a powdery composite positive electrode active material, and also to a lithium ion battery positive electrode sheet and a lithium ion battery comprising the powdery composite positive electrode active material. Background Art
[0002] Lithium-ion batteries have been widely used in electric vehicles, spacecraft, variable electronic devices, etc. due to their advanced characteristics such as high energy density, high conversion efficiency and long cycle life. At the same time, increasingly in-depth application scenarios have also prompted lithium-ion batteries to develop in the direction of high energy density and long cycle life.
[0003] The performance of lithium-ion batteries directly depends on the positive electrode material. The nickel-cobalt-manganese-oxide ternary material that can be used as the positive electrode material of lithium-ion batteries combines the advantages of Ni, Co and Mn, and has greater potential to obtain specific capacity, power density and energy density. Generally speaking, increasing the nickel content in the ternary material will increase its specific capacity. For example, the nickel-rich ternary material LiNi with a Ni content of 80% 0.8 Co 0.1 Mn 0.1 O2 (also known as NCM811) has a high specific capacity (approximately ≥250mAh / g) and is the main material used in commercial power batteries.
[0004] However, since the electrolyte will produce hydrogen fluoride (HF) after oxidation at high potential, it may dissolve the transition metal in the positive electrode material, causing irreversible capacity loss of the material, thereby significantly reducing the energy density and cycle life. Therefore, improving the interfacial stability of the positive electrode material to prevent HF corrosion and form a thicker solid electrolyte interface layer (SEI) is one of the important methods to improve the energy density and cycle life of high-nickel ternary materials.
[0005] Oxides as coating modification materials have the characteristics of a wide variety, stable structure, reduced interface side reactions and prevention of oxygen loss. However, HF corrosion in the high voltage range will produce some fluorides, causing the oxide coating to fall off.
[0006] Using lithium fluoride (LiF), one of the components of SEI, as a coating layer can prevent the positive electrode material from being corroded by the electrolyte, inhibit the growth of SEI film, and improve the material cycle performance. At the same time, LiF has good chemical stability and can maintain performance under different environmental conditions, which is beneficial to the long-term stability of the battery.
[0007] However, the LiF coating also faces some difficulties and challenges in practical applications: for example, the uniformity problem, the uneven coating will affect the performance of the battery; and the coating thickness control problem, the thickness of the LiF coating needs to be precisely controlled, too thick may affect the transmission of lithium ions, too thin may not provide sufficient protection.
[0008] In addition, how to optimize the performance of the composite positive electrode active material coated with the LiF coating layer is also a problem that needs to be solved in the art. Summary of the invention
[0009] Purpose of the Invention
[0010] In view of the problems existing in the prior art described in the above background technology section, the object of the present invention is to provide a powdery composite positive electrode active material with a LiF coating layer on the surface and a preparation method thereof. The object of the present invention is also to provide a lithium ion battery positive electrode sheet comprising the powdery composite positive electrode active material and a lithium ion battery comprising the lithium ion battery positive electrode sheet.
[0011] Technical Solution
[0012] In order to achieve the above object, the present invention adopts the following technical solutions:
[0013] Option 1: A powdered composite positive electrode active material, comprising a nickel-rich ternary material as a core, and a lithium fluoride coating layer coated on the surface of the nickel-rich ternary material, wherein the primary particle size of the powdered composite positive electrode active material is in the range of about 3 μm to about 8 μm, and wherein the lithium fluoride coating layer is formed by a powder atomic layer deposition process.
[0014] Option 2: The powdery composite positive electrode active material according to Option 1 above, wherein the thickness of the lithium fluoride coating layer is in the range of 1 nm to 1000 nm.
[0015] Scheme 3: A method for a powdered composite positive electrode active material according to any one of Schemes 1 to 2 above, wherein the nickel-rich ternary material comprises LiNi x Co y Mn z O2, where x+y+z=1, and x≥0.6.
[0016] Scheme 4: A method for a powdered composite positive electrode active material according to any one of Schemes 1 to 3 above, wherein the nickel-rich ternary material comprises NCM811.
[0017] Scheme 5: A method for preparing a powdered composite positive electrode active material according to any one of Schemes 1 to 4 above, wherein the method comprises the following steps:
[0018] Step 1: placing the nickel-rich ternary material powder as a core into a reaction chamber of a powder coating instrument, wherein the nickel-rich ternary material powder has a primary particle size ranging from about 3 μm to about 8 μm;
[0019] Step 2: heating the nickel-rich ternary material powder in the reaction chamber to about 200 to about 300° C. in an inert gas atmosphere at a pressure lower than about 1.7 KPa;
[0020] Step 3: Filling the reaction chamber with an excess of lithium precursor gas to saturate and adsorb the lithium precursor gas on the surface of the nickel-rich ternary material powder;
[0021] Step 4: Filling the reaction chamber with an inert gas to purge the reaction chamber, thereby taking away excess lithium precursor gas in the reaction chamber; and
[0022] Step 5: Filling the reaction chamber with an excess of fluorine source gas to react with the lithium precursor adsorbed on the surface of the nickel-rich ternary material powder to generate the lithium fluoride coating layer.
[0023] Scheme 6: A preparation method according to Scheme 5 above, wherein the lithium precursor comprises one or more of lithium tert-butoxide and lithium tetramethylheptanedione.
[0024] Scheme 7: A preparation method according to Scheme 5 or 6 above, wherein the fluorine source comprises titanium tetrafluoride.
[0025] Scheme 8: The preparation method according to any one of Schemes 5 to 7 above, wherein the oxygen concentration in the inert gas atmosphere in step 2 is less than about 25% by volume.
[0026] Scheme 9: A preparation method according to any one of Schemes 5 to 8 above, wherein the method further comprises step 6 performed after step 5: filling the reaction chamber with an inert gas to clean the reaction chamber of excess fluorine source and reaction by-products.
[0027] Scheme 10: A preparation method according to Scheme 9 above, wherein steps 1 to 6 are repeated multiple times until a lithium fluoride coating layer of a desired thickness is obtained.
[0028] Scheme 11: A lithium-ion battery positive electrode sheet comprising a powdered composite positive electrode active material according to any one of Schemes 1 to 4 above or a powdered composite positive electrode active material prepared by the preparation method according to any one of Schemes 5 to 10 above.
[0029] Scheme 12: A lithium-ion battery comprising the lithium-ion battery positive electrode sheet according to Scheme 11 above.
[0030] Scheme 13: Use of a powder atomic layer deposition process for preparing a powdered composite positive electrode active material according to any one of Schemes 1 to 4 above.
[0031] Technical Effects
[0032] The present invention adopts the powder atomic layer deposition (PALD) process to synthesize a high nickel ternary material with a LiF coating layer with uniform and controllable thickness on the surface at a relatively low temperature. The powder composite positive electrode material of the present invention has the following advantages:
[0033] 1: LiF is one of the main components of SEI, has good chemical stability, and good compatibility with electrolyte. Using LiF, one of the components of SEI, as a coating layer can prevent the positive electrode material from being corroded by the electrolyte, inhibit the growth of SEI film, and improve the material cycle performance. At the same time, LiF has good chemical stability and can maintain performance under different environmental conditions, which is beneficial to the performance, safety and long-term stability of the battery.
[0034] 2: The PALD process can deposit a LiF coating layer with highly uniform thickness and excellent conformality on the positive electrode material, which is conducive to the formation of a stable SEI. At the same time, PALD can achieve atomic-level thickness control. For example, the coating thickness can increase by about 0.3 to about 100% after one cycle. For example, about The thickness of the coating layer formed is uniform and can be precisely adjusted by controlling the number of cycles, thus better optimizing battery performance and reducing material usage.
[0035] 3: The synthesis temperature of the PALD process is low, which reduces the impact of heat treatment in the coating stage on the crystal structure and size of the base material and the lithium-nickel mixing. At the same time, it consumes less energy and has lower production costs.
[0036] 4: The powdered composite positive electrode active material having a primary particle size within the range specified in the present invention can have improved cycle performance while taking into account good compaction and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the specific implementation modes of the present invention, the drawings required for use in the specific implementation modes will be briefly introduced below. Obviously, the drawings described below are some implementation modes of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0038] Figure 1 The present invention schematically illustrates a process for synthesizing a powdered composite positive electrode active material using a powder atomic layer deposition process.
[0039] Figure 2 This is an electron microscope photograph of the powdery NCM811 with a LiF coating layer according to Example 1 of the present invention.
[0040] Figure 3 The cycle performance test results of button cells prepared from the powdered composite positive electrode active materials of Examples 1 and 2 of the present invention and Comparative Examples 1 to 4 are shown. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without paying creative work belong to the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on normal conditions.
[0042] The endpoints and any values of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values should be understood to include values close to these scopes or values. The term "about" used in the present invention means that the modified numeral can fluctuate within the range of ±20%, ±15%, ±10%, ±5% or ±2% of the numeral. For numerical ranges, the endpoint values of each scope, the endpoint values of each scope and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in the present invention.
[0043] According to a first aspect of the present invention, the present invention provides a powdery composite positive electrode active material.
[0044] The powdery composite positive electrode active material according to the first aspect of the present invention comprises a nickel-rich ternary material as a core, and a lithium fluoride coating layer coated on the surface of the nickel-rich ternary material.
[0045] In the powdered composite positive electrode active material of the first aspect of the invention, the nickel-rich ternary material can be a nickel-rich ternary material commonly used in lithium-ion batteries in the art, preferably LiNi x Co y Mn z O2, wherein x+y+z=1, and x≥0.6, for example, x is 0.7, 0.8 or 0.9. In a specific embodiment of the present invention, the nickel-rich ternary material used comprises LiNi 0.8 Co 0.1 Mn 0.1 O2, that is, NCM811.
[0046] In the powdered composite positive electrode active material of the first aspect of the invention, the thickness of the lithium fluoride coating layer can be freely selected by those skilled in the art according to actual needs. For example, in some exemplary embodiments of the present invention, the thickness can be determined to be in the range of about 1 nm to about 1000 nm, for example, about 2 to about 100 nm, specifically about 3 to about 10 nm, and more specifically about 5 nm. Here, the thickness of the lithium fluoride coating layer should not be too large, for example, it should not exceed about 1000 nm, otherwise the lithium ions (Li + )The increase in diffusion distance will affect Li + transmission; nor should it be too small, for example, not less than about 1 nm, otherwise it may not provide sufficient protection for the nickel-rich ternary material.
[0047] The thickness of the lithium fluoride coating on the surface of the nickel-rich ternary material should be uniform, so it is preferred to form the lithium fluoride coating using a powder atomic layer deposition process. The powder atomic layer deposition process is to supply and clean two different precursors into the reaction chamber in turn, control the flow rate and time of the precursors, and the subsequent flushing to control the amount of precursors deposited on the surface. After the deposition reaction on the surface, a controllable thin film coating layer with atomic-level thickness is deposited layer by layer on the surface of the substrate. The powder atomic layer deposition has many advantages as described in the "Technical Effects" section above, especially the uniform and controllable layer thickness.
[0048] The powdered composite positive active material according to the first aspect of the present invention should have a primary particle size in the range of about 3 μm to about 8 μm. Generally speaking, a positive electrode material with a primary particle size within the defined range (about 3 μm to about 8 μm) has a higher surface area than a positive electrode material with a larger particle size (about> 8 nm), a larger contact area with the electrolyte, and a more obvious side reaction. Therefore, after coating the LiF coating layer, the LiF coating layer has a larger area and the cycle performance improvement effect will be more obvious. However, the primary particle size of the powdered composite positive active material should not be too small, for example, it should not be less than about 3 μm. Such positive electrode material particles are easily agglomerated into larger particles, resulting in the coating layer being not dense enough, and the difficulty of dispersion during the production process is greater, which will reduce the cycle performance.
[0049] According to the second aspect of the present invention, the present invention provides a method for preparing a powdered composite positive electrode active material according to the first aspect of the present invention. The preparation method described in the second aspect of the present invention is actually a method for forming the powdered composite positive electrode active material using the PALD process described above. The preparation method of the present invention includes the following steps 1 to 5.
[0050] The step 1 includes placing the nickel-rich ternary material powder as the core into a reaction chamber of a powder coating instrument, wherein the primary particle size of the nickel-rich ternary material powder needs to ensure that the powdered composite positive electrode active material obtained therefrom has a primary particle size in the range of about 3 μm to about 8 μm. Considering that the thickness of the lithium fluoride coating layer is only nanometer-level, the nickel-rich ternary material powder also preferably has a primary particle size in the range of about 3 μm to about 8 μm.
[0051] The step 2 comprises heating the nickel-rich ternary material powder in the reaction chamber to about 200 to about 300° C., for example, about 250° C., in an inert gas atmosphere at a pressure lower than about 1.7 KPa.
[0052] Here, in order to make the subsequent adsorption and reaction proceed smoothly, the nickel-rich ternary material powder needs to be placed in an inert gas atmosphere, such as a nitrogen atmosphere. The oxygen concentration in the inert gas atmosphere is preferably less than about 25% by volume. Too high an oxygen concentration, such as greater than about 25% by volume, may cause the vacuum pump oil tank to catch fire and explode.
[0053] In addition, in order to allow the subsequent adsorption and reaction to proceed smoothly, the temperature of the nickel-rich ternary material powder needs to be heated to a range of about 200 to about 300°C.
[0054] The step 3 includes charging an excess amount of lithium precursor gas into the reaction chamber so that the lithium precursor gas is saturated and adsorbed on the surface of the nickel-rich ternary material powder.
[0055] Here, the lithium precursor may be an organic lithium salt commonly used in the art, including but not limited to one or more of lithium tert-butoxide and lithium tetramethylheptanedione.
[0056] In addition, the amount of lithium precursor gas charged into the reaction chamber needs to ensure that at least one layer of lithium precursor molecules is uniformly adsorbed on all surfaces of the nickel-rich ternary material powder. For example, in a specific embodiment of the present invention, for a reaction chamber volume of about 200 mL and about 10 g of nickel-rich ternary material powder having a primary particle size in the range of about 3 μm to about 8 μm, the flow rate of the lithium precursor gas charged is about 100 to about 200 sscm, for example, about 120 sscm, and the time is about 0.9 to about 1.1 seconds, for example, about 1.0 seconds.
[0057] The step 4 includes filling the reaction chamber with an inert gas to purge the reaction chamber, thereby taking away excess lithium precursor gas in the reaction chamber.
[0058] Here, the inert gas may include nitrogen. The amount of the inert gas filled should be sufficient to take away the excess lithium precursor gas in the reaction chamber. For example, in a specific embodiment of the present invention, for a reaction chamber volume of about 200 mL and about 10 g of nickel-rich ternary material powder, the flow rate of the inert gas filled into the reaction chamber may be about 150 to about 250 sccm, such as about 200 sscm, for 10 to 20 seconds, such as about 15 seconds.
[0059] The step 5 includes charging an excess amount of fluorine source gas into the reaction chamber to react with the lithium precursor adsorbed on the surface of the nickel-rich ternary material powder to generate the lithium fluoride coating layer.
[0060] Here, the fluorine source may be a fluorine-containing compound commonly used in the art, including but not limited to titanium tetrafluoride.
[0061] In addition, the amount of fluorine source gas charged into the reaction chamber needs to ensure that the lithium precursor molecules adsorbed on the surface of the nickel-rich ternary material powder react with the fluorine source molecules. For example, in a specific embodiment of the present invention, for a reaction chamber volume of about 200 mL and about 10 g of nickel-rich ternary material powder with a primary particle size ranging from about 3 μm to about 8 μm, the flow rate of the fluorine source gas charged is about 100 to about 200 sscm, for example, about 150 sscm, and the time is about 0.09 to about 0.11 seconds, for example, about 0.1 seconds.
[0062] Preferably, the preparation method according to the second aspect of the present invention further comprises performing step 6 after steps 1 to 5.
[0063] The step 6 includes charging the reaction chamber with an inert gas to clean the excess fluorine source and reaction by-products in the reaction chamber. Here, in order to further coat another lithium fluoride layer on the nickel-rich ternary material that has been coated with one or more lithium fluoride coating layers, the above steps 1 to 5 need to be repeated, and therefore, the excess fluorine source and reaction by-products in the reaction chamber need to be removed to avoid subsequent deposition failure.
[0064] Here, the inert gas may include nitrogen. The amount of the inert gas filled should be sufficient to take away the excess fluorine source gas and reaction byproducts in the reaction chamber. For example, in a specific embodiment of the present invention, for a reaction chamber volume of about 200 mL and about 10 g of nickel-rich ternary material powder, the flow rate of the inert gas filled into the reaction chamber may be about 100 to about 200 sccm, such as about 120 sscm, and the time is 10 to 20 seconds, such as about 15 seconds.
[0065] Further preferably, the preparation method according to the second aspect of the present invention also comprises repeating the above-mentioned steps 1 to step 6 for many times until obtaining the lithium fluoride coating layer of desired thickness.Herein, those skilled in the art can determine the number of times of desired cyclic repetition according to the actual required lithium fluoride coating layer thickness.For example, in a specific embodiment of the present invention, for realizing the lithium fluoride coating layer thickness of about 5nm, the described circulation can be repeated about 100 times.
[0066] According to the third aspect of the present invention, the present invention provides a lithium ion battery positive electrode sheet comprising a powdered composite positive electrode active material according to the first aspect of the present invention or a powdered composite positive electrode active material prepared according to the preparation method described in the second aspect of the present invention.
[0067] According to a fourth aspect of the present invention, the present invention provides a lithium ion battery comprising the lithium ion battery positive electrode sheet according to the third aspect of the present invention.
[0068] According to a fifth aspect of the present invention, the present invention also provides the use of a powder atomic layer deposition process for preparing the powdered composite positive electrode active material according to the first aspect of the present invention.
[0069] The present invention is further described in detail below with reference to specific embodiments and comparative examples.
[0070] The raw materials used in the following examples and comparative examples were all commercially available analytically pure products.
[0071] Example 1: Preparation of powdered composite NCM811 using a powder coating instrument
[0072] The powder coating instrument comprises a control cabinet, a reaction chamber, an evaporation chamber and a vacuum system (vacuum chamber, vacuum gauge, magnetic coupling rotator, vacuum pipeline, pre-pump filter and vacuum pump).
[0073] Before starting the preparation, the vacuum tightness of the reaction chamber is first checked, and then about 10g of powdered positive electrode active material NCM811 is loaded into the reaction chamber. The primary particle size of the positive electrode active material NCM811 is in the range of about 3μm to about 8μm. The accumulated volume of the positive electrode active material NCM811 does not exceed about one-fifth of the volume of the reaction chamber (about 200mL).
[0074] The present invention specification is then attached Figure 1 The schematic process shown is for the preparation of powdered composite positive electrode active material (NCM811):
[0075] (1) The reaction chamber is evacuated to a vacuum state with a pressure of about 1.7 MPa or less by using a vacuum system, and then filled with nitrogen for replacement, and then evacuated to a vacuum state, and this cycle is repeated three times, and the volume concentration of oxygen in the reaction chamber is reduced to less than 25% by volume by using nitrogen. At the same time, the reaction chamber is heated and kept warm, and the heating temperature is in the range of about 200 to about 300°C.
[0076] (2) introducing lithium tert-butoxide vapor as a lithium precursor at a gas flow rate of about 120 sscm for about 1 second, and then evacuating the gas;
[0077] (3) nitrogen gas is introduced at a flow rate of about 200 sscm to purge the reaction chamber with nitrogen gas to remove excess precursor vapor. The purge time is about 15 seconds.
[0078] (4) introducing titanium tetrafluoride (TiF4) at a gas flow rate of about 150 sscm for about 0.1 second, at which time, lithium tert-butoxide saturatedly adsorbed on the surface of granular NCM811 reacts with TiF4, and the reaction temperature is maintained in the temperature range of about 200 to about 300° C. during the reaction, and then vacuuming;
[0079] (5) nitrogen is again charged at a gas flow rate of about 120 sscm to clean the unreacted excess TiF4 and the generated reaction by-products. The cleaning time is about 15 seconds. At this time, the first round of coating of NCM811 is completed.
[0080] (6) Repeat the above steps (2) to (5) for about 100 times to obtain a multi-coated NCM811 sample. Cool the system, open the bin and take out the material to obtain the sample of Example 1.
[0081] Electron microscope photo of the sample of Example 1 (see the appendix of the specification of the present invention) Figure 2 ) shows that a nanometer-level LiF coating layer was successfully coated on the surface of the NCM811 substrate material. According to the electron microscope photos, the prepared coating layer has very good conformality, which is mainly due to the fact that the precursor material is introduced into the reaction chamber in the form of gas and is closely combined with the substrate material.
[0082] The primary particle size of the powdery composite positive electrode active material obtained in Example 1 is in the range of about 3 μm to about 8 μm, wherein the thickness of the lithium fluoride coating layer is about 5 nm.
[0083] Embodiment 2:
[0084] The powdered composite NCM811 was prepared in the same process as in Example 1, except that lithium tert-butoxide as a lithium precursor was replaced with lithium tetramethylheptanedionate.
[0085] The primary particle size of the powdery composite positive electrode active material obtained in Example 2 is in the range of about 3 μm to about 8 μm, wherein the thickness of the lithium fluoride coating layer is about 5 nm.
[0086] Comparative Example 1:
[0087] The powdered composite NCM811 was prepared in the same process as in Example 1, except that the primary particle size of the positive electrode active material NCM811 used was in the range of about 10 μm to about 20 μm.
[0088] The primary particle size of the powdery composite positive electrode active material obtained in Comparative Example 1 is in the range of about 10 μm to about 20 μm, wherein the thickness of the lithium fluoride coating layer is about 5 nm.
[0089] Comparative Example 2:
[0090] The powdered composite NCM811 was prepared in the same process as in Example 1, except that the primary particle size of the positive electrode active material NCM811 used was in the range of about 1 μm to about 2 μm.
[0091] The primary particle size of the powdery composite positive electrode active material obtained in Comparative Example 2 is in the range of about 1 μm to about 2 μm, wherein the thickness of the lithium fluoride coating layer is about 5 nm.
[0092] Comparative Example 3: Preparation of powdered composite NCM811 by solvent thermal method
[0093] About 0.05 mL of trifluoroacetic acid is dispersed in about 20 mL of methanol, and then about 2 g of powdered NCM811 is added. The primary particle size of the positive electrode active material NCM811 is in the range of about 3 μm to about 8 μm. After stirring evenly, it is placed in a water bath at about 40°C and evaporated to dryness. The obtained solid product is calcined in a muffle furnace at a temperature of about 650°C for about 2 hours. Here, first, the lithium carbonate on the surface can react with trifluoroacetic acid to form lithium trifluoroacetate, which is further decomposed to form lithium fluoride in the subsequent calcination. Secondly, trifluoroacetic acid is a strong acid and can also react similarly with lithium cobalt oxide to form lithium fluoride. After the obtained material is naturally cooled, a powdered composite NCM811 with a lithium fluoride coating layer on the surface is obtained.
[0094] The primary particle size of the powdery composite positive electrode active material obtained in Comparative Example 3 is in the range of about 3 μm to about 8 μm, wherein the thickness of the lithium fluoride coating layer is about 20 nm.
[0095] Comparative Example 4: Preparation of powdered composite NCM811 by chemical vapor deposition
[0096] About 10g of powdered NCM811 was spread in a corundum boat, and the primary particle size of the positive electrode active material NCM811 was in the range of about 3μm to about 8μm. The powdered NCM811 was subjected to low-temperature gas phase treatment, and the gas for low-temperature gas phase treatment was a nitrogen trifluoride / argon mixed gas, wherein the content of nitrogen trifluoride was about 10% by volume; the gas flow rate was about 80sccm; the ventilation time was about 30 minutes, and the treatment temperature was about 200°C. Since there was residual alkali (lithium carbonate and lithium hydroxide) on the surface of NCM811, a powdered composite NCM811 coated with a lithium fluoride coating layer was obtained.
[0097] The primary particle size of the powdery composite positive electrode active material obtained in Comparative Example 4 is in the range of about 3 μm to about 8 μm, wherein the thickness of the lithium fluoride coating layer is about 3 nm.
[0098] Battery Assembly
[0099] The powdered composite NCM811 obtained from Examples 1 and 2 and Comparative Examples 1 to 4 were mixed with acetylene black conductive agent and PVDF binder in a mass ratio of about 8:1:1 in NMP solvent to form a uniform slurry, and the slurry was evenly coated on aluminum foil with a coating surface density of about 5 mg / cm 2 Then, the aluminum foil was placed in a vacuum drying oven and dried at about 80°C for about 12 hours. The dried aluminum foil with the positive electrode material was cut into pieces with an area of about 2 cm 2 The disc is made into the working electrode and assembled into a button battery with commonly used metallic lithium as the negative electrode.
[0100] Performance Testing
[0101] Electrochemical testing:
[0102] At room temperature, the charge and discharge voltage range was set to about 3.0 to about 4.3 V. Cyclic tests were performed at a current density of about 1C, and the capacity retention rate was calculated: the capacity retention rate at the Xth week = the cycle discharge capacity at the Xth week / the first discharge capacity. The DCR of the button cell was tested after every 200 cycles. Three samples were tested in parallel for each group of batteries.
[0103] The DCR changes of the batteries prepared by the positive electrode materials of Example 1 and Comparative Examples 1 to 4 were tested, wherein the DCR test was performed once every 200 cycles of the cycled batteries. The test results are shown in Table 1 below. The unit of the measured DCR results in Table 1 is ohm (Ω).
[0104] Table 1
[0105] Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 0 laps 24.65 25.24 25.94 23.48 27.30 25.67 200 laps 30.18 29.19 32.34 29.89 34.04 31.81 400 laps 34.88 35.40 40.03 36.49 42.14 37.35 600 laps 39.63 40.77 46.82 42.41 49.28 48.66 800 laps 44.61 45.41 52.10 48.57 54.84 53.65
[0106] It can be seen from the result data in Table 1 that the DCR growth rate of the powdered composite positive electrode active material (Examples 1 and 2) synthesized by the PALD process of the present invention is significantly lower than that of the materials prepared by the conventional solvothermal method and chemical vapor deposition method (Comparative Examples 3 and 4), and is also lower than that of the powdered composite positive electrode active material with a larger or smaller primary particle size (Comparative Examples 1 and 2), indicating that within the appropriate particle size range, the powdered composite positive electrode active material synthesized by the PALD process has fewer side reactions and smaller internal resistance changes during the cycle, thereby proving that the LiF coating layer prepared by the PALD process can well prevent the positive electrode material from contacting the electrolyte and hindering the electrolyte erosion, and has better long cycle performance.
[0107] The cycle performance of the batteries prepared from the positive electrode materials of Examples 1 and 2 and Comparative Examples 1 to 4 is shown in the attached figure of the specification of the present invention. Figure 3 In. Figure 3 As shown, the materials of Examples 1 and 2 synthesized by the PALD process of the present invention have the best cycle stability, which is significantly better than the materials coated on the positive electrode materials with larger or smaller primary particles and the materials prepared by conventional solvothermal method and chemical vapor deposition method. This is mainly due to the following reasons:
[0108] 1: The positive electrode material with a primary particle size within an appropriate range (about 3 to about 8 nm) has a higher surface area than the positive electrode material with a larger primary particle size (about > 8 nm), a larger contact area with the electrolyte, more obvious side reactions, and a larger LiF coating area after coating, for example, a more obvious improvement in cycle performance.
[0109] 2: However, the primary particles of the positive electrode material are smaller (about <3nm) and tend to agglomerate into large particles, resulting in an insufficiently dense coating layer and difficulty in dispersion during the production process, which in turn reduces the cycle performance.
[0110] 2: The PALD process has a lower synthesis temperature, which reduces the impact of heat treatment in the coating stage on the crystal structure and size of the substrate material.
[0111] 3: The LiF coating layer with appropriate thickness and good consistency prevents the contact between the positive electrode material and the electrolyte and hinders the corrosion of the electrolyte. At the same time, it will not increase the LiF coating layer due to excessive thickness. + Diffusion distance.
[0112] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions claimed to be protected by the present invention.
Claims
1. A powdery composite positive electrode active material, characterized in that: The composite positive electrode active material comprises a nickel-rich ternary material as a core, and a lithium fluoride coating layer coated on the surface of the nickel-rich ternary material. The primary particle size of the powdered composite positive electrode active material is in the range of 3 μm to 8 μm, and the lithium fluoride coating layer is formed by a powder atomic layer deposition process.
2. The powdery composite positive electrode active material according to claim 1, characterized in that: The thickness of the lithium fluoride coating layer is in the range of 1 nm to 1000 nm.
3. The method for preparing a powdery composite positive electrode active material according to claim 1 or 2, characterized in that: The nickel-rich ternary material comprises LiNi x Co y Mn z O2, wherein x+y+z=1, and x≥0.6, preferably comprises NCM811.
4. A method for preparing a powdery composite positive electrode active material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: Step 1: placing the nickel-rich ternary material powder as a core into a reaction chamber of a powder coating instrument, wherein the nickel-rich ternary material powder has a primary particle size ranging from 3 μm to 8 μm; Step 2: heating the nickel-rich ternary material powder in the reaction chamber to 200 to 300° C. in an inert gas atmosphere at a pressure lower than 1.7 KPa; Step 3: Filling the reaction chamber with an excess of lithium precursor gas to saturate and adsorb the lithium precursor gas on the surface of the nickel-rich ternary material powder; Step 4: Filling the reaction chamber with an inert gas to purge the reaction chamber, thereby taking away excess lithium precursor gas in the reaction chamber; and Step 5: Filling the reaction chamber with an excess of fluorine source gas to react with the lithium precursor adsorbed on the surface of the nickel-rich ternary material powder to generate the lithium fluoride coating layer.
5. The preparation method according to claim 4, characterized in that: The lithium precursor comprises one or more of lithium tert-butoxide and lithium tetramethylheptanedione; and / or The fluorine source comprises titanium tetrafluoride.
6. The preparation method according to claim 4 or 5, characterized in that: The oxygen concentration in the inert gas atmosphere in step 2 is lower than 25% by volume.
7. The preparation method according to claim 4 or 5, characterized in that: The method further comprises a step 6 performed after the step 5: filling the reaction chamber with an inert gas to clean the reaction chamber of excess fluorine source and reaction by-products.
8. The preparation method according to claim 7, characterized in that: Repeat steps 1 to 6 multiple times until a lithium fluoride coating layer of desired thickness is obtained.
9. A positive electrode sheet for a lithium ion battery comprising the powdery composite positive electrode active material according to claim 1 or 2 or the powdery composite positive electrode active material prepared by the preparation method according to any one of claims 3 to 8.
10. A lithium ion battery comprising the lithium ion battery positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Battery positive electrode material, battery positive plate and lithium battery
CN110048111A
Preparation method of lithium fluoride in-situ coated high-nickel ternary positive electrode material
CN113764634A
Multi-dimensional composite coated positive electrode material as well as preparation method and application thereof
CN118198304A